Household Solid Fuel Use and Associated Factors in Somaliland: A Multilevel Analysis of Data From 2020 Somaliland Demographic and Health Survey - Mustafe Abdillahi Ali; Abdirizak Hassan Abokor; Omer Adam Farih; Hodo Abdikarim; Abdirashid M Yousuf; Abdisalam Hassan Muse (Environmental Health Insights)
This study, utilizing data from the 2020 Somaliland Demographic and Health Survey, investigates the prevalence of household solid fuel use in Somaliland and the factors associated with this practice. Our analysis reveals that a staggering 97.2% of households rely on solid fuels like wood and charcoal for cooking, with only 2.8% utilizing clean energy sources. We employed multilevel logistic regression to examine the influence of individual and community-level variables on fuel choice. Results highlight the significant roles of education level, gender of the household head, wealth status, and location of cooking in shaping fuel selection. The study, aligned with Sustainable Development Goal 7: Affordable and Clean Energy, emphasizes the urgency of promoting clean energy alternatives, improving cooking practices, and addressing the health and environmental impacts of solid fuel usage to foster a more sustainable energy landscape in Somaliland.